2020
DOI: 10.1007/s10875-020-00834-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous TLR3 Mutation in Patients with Hantavirus Encephalitis

Abstract: Puumala hantavirus (PUUV) hemorrhagic fever with renal syndrome (HFRS) is common in Northern Europe; this infection is usually self-limited and severe complications are uncommon. PUUV and other hantaviruses, however, can rarely cause encephalitis. The pathogenesis of these rare and severe events is unknown. In this study, we explored the possibility that genetic defects in innate anti-viral immunity, as analogous to Toll-like receptor 3 (TLR3) mutations seen in HSV-1 encephalitis, may explain PUUV encephalitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Alexeyev et al reported cases of meningism, epileptic seizures, urinary bladder paralysis, and cerebral hemorrhage in their NE patient cohort [10]. Seizures, confusion, somnolence, and vision loss, mainly among young male patients, have also been reported [8,13,14]. These reports highlight the potential of the acute NE to cause serious and possibly irreversible CNS complications.…”
Section: Cns and Acute Ne 21 Cns Symptomsmentioning
confidence: 95%
See 3 more Smart Citations
“…Alexeyev et al reported cases of meningism, epileptic seizures, urinary bladder paralysis, and cerebral hemorrhage in their NE patient cohort [10]. Seizures, confusion, somnolence, and vision loss, mainly among young male patients, have also been reported [8,13,14]. These reports highlight the potential of the acute NE to cause serious and possibly irreversible CNS complications.…”
Section: Cns and Acute Ne 21 Cns Symptomsmentioning
confidence: 95%
“…Acute NE may rarely present symptoms and findings consistent with viral encephalitis criteria such as altered mental status or generalized seizures [15]. Moreover, abnormalities of brain parenchyma on neuroimaging and on electroencephalography have been reported [8,10,13,14]. Based on personal unpublished clinical experience, most NE encephalitis patients recover well without long-term sequelae.…”
Section: Puuv Encephalitismentioning
confidence: 99%
See 2 more Smart Citations
“…TLR3 p.L742F variant is in vitro severely hypomorphic based on experiments on TLR3-deficient P2.1 fibrosarcoma cell line, and the production of IFN-λ and interleukin-6 in response to TLR3 activation by poly(I:C) stimulation was impaired in previously tested SV40 immortalized human skin fibroblasts heterozygous for this variation. 6 She was also found to be positive for TRF1-interacting nuclear factor 2 ( TINF2 ) variant p.Y312* (rs201677741) previously associated with Ewing sarcoma. Pathogenic TINF variants are associated with autosomal dominant dyskeratosis congenita and pathologic telomere lengths (OMIM 604319).…”
mentioning
confidence: 96%